Kontribusi Usaha Kopra terhadap Pendapatan Petani di Desa Munse Indah Kecamatan Wawonii Timur Kabupaten Konawe - Riansyah, Riansyah; Iswandi, R. Marsuki; Suriana, Suriana (Jurnal Ilmiah Membangun Desa dan Pertanian, 2018)
The study aims to assess the amount of Copra income, the total income of Farmers and compare the total income with the provincial minimum (UMP) in Southeast Sulawesi, the contribution of the copra business to the farmers based on the pattern of farming in an effort. The problem faced by farmers in processing coconut into copra. This research is executed on the month of November 2016 – May 2017. Sample research conducted by random sampling with population amounted about 143 peoples in this research sampling amounted to 36 respondent data analysis using qualitative and quantitative analysis. The results showed that the average income of copra business respondent was Rp 580.385 of the month. Revenue in the village of Munse Indah is higher than the minimum wage of Southeast Sulawesi Province of Rp 2.002.065. The contribution of the copra business to the total income of the farmers based on the pattern of farming in the effort, the pattern of farming (coconut, cashew, cloves, rice fields and nutmeg) gave the highest contribution of 49,05% with the medium criteria than on the pattern of farming (coconut, cashew, cloves, rice fields and nutmeg) gave the lowest contribution about 22,68% with the lowest criteria. The problems faced by farmers in processing coconut into copra there are three things, namely lack of climber, lack op owned capital and access road damaged in the rainy season.